Jornal das Moças: leitura, civilidade e educação femininas (1932-1945). - Almeida, Nukácia Meyre Araújo (2008)
The present paper aims at analyzing the way how a textual support, whose communicative purpose is not determining norms and orders, performs among social conventions that are, little by little, absorbed by women. The analysis starts from a point of view that assemblies the History of Reading perspective and follows, consequently, with the History of Education, Sociology - with a historical basis, Linguistics and Discourse Analysis. The support chosen as a research source was “ Jornal das Moças”, a female magazine published in Rio de Janeiro from 1914 to 1965. The corpus consists of the publications from 1932 to 1945. The concept of civility, or the group of adequately social behaviors, leads our description and the support analysis. The concepts of ethos and of incorporation grounds the discourse of civility’s analysis, one of the files presented in the magazine. The results of the support analysis confirm the conduct assignments considered adequate to women in the 30’s and 40’s. Some social roles such as mother, housewife, wife and tutor are reasserted through many discourse genres which appears along the magazine and through the iconography present in many of the magazine texts. The analyzed genres which are surrounded by the civility concept are the short story, advertisement, advisement, and articles. The ethé of beauty and of reservedness; abnegation; dedication; submission and health; and wisdom evocate, respectively, the figures of woman, mother, housewife, wife and best tutor. The incorporation of adequate behaviors to the social roles predicted for women is obtained through the utterer’s ethos assimilation, by the adhesion to the announced ideas and by the representation of others social actors built in the discourse.